Contemporary living in Asia - Gerritsen, Marc. (Singapore : Page One Publishing Pte Ltd., 2011)
This book shows a selection of his most recent work in Asia: a constant search for perfect design, balanced proortions and excelling in restraint and discrete, refined beauty.
Kunlun apartment, Beijing -- The Palace apartment in Taipei -- An apartment with a view on Renai Road -- Blue Ocean building -- Da-an residence -- Spectacular views of the South China Sea in Hong Kong -- Tsai's residence, Taipei -- Nankang apartment, Taipei --Yongtai Xianshang residence, Haidian district, Beijing -- Chendu House, Western China.
Keywords: ARCHITECTURE -- ASIA -- HISTORY